(3GdehGdjO CMcGegGs - (3RQGOTJ , Mcje GdaQSs ((3eMeO Hf Ydi GdHbGQ s)
(3ChdgG (B:s
(3bGd egG fcQO Hf egQHGf (B: (3gPG SQ ef fHhAI RQGOTJ HYK Hg dHjGf GdfhQ ai eSGeY RQGOTJ s
(3BNQgG (B:s
(3gPg efGRd GdchGcH ai ReGf SYjO Hf NQGSGfi hgh GdPi hVY GdeKGd hGNJUQfGg hGbJUQgG Hg Ydi gPjf GdchcHjf hGddg Gdehab ddUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3HgG fXGe GdJYbjHIs
(3HChdgG UaMI ai JQLeI RQGOTJs
(3ai GdeYgO fSNI CNQi HQbe (B124 (3adcs
(3cJHJ gPg GdfSNI HQSe eMeO Hf Ydi Hf EOQjS Gdchei s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs